IMPACTS OF ECONOMIC VARIABLES ON SUSTAINABLE ENERGY CONSUMPTION IN VIETNAM - Hong, Nguyen Thi; Hoang, Nguyen Cong; Linh, Khuat Vu Ngoc (Graduate Program of Universitas Tarumanagara, 2024)
Amidst the global energy crisis and Vietnam's rapid industrialization, this paper explores the imperative to transition towards sustainable energy consumption. With Vietnam's substantial surge in energy demand, the need for sustainable alternatives becomes paramount. Drawing upon an extensive review, this study examines the economic variables influencing sustainable energy consumption in Vietnam. It reveals nuanced impacts of GDP per capita, Foreign Direct Investment (FDI), industrial manufacturing (MNF), Gross Capital Formation (GCF), and Trade Openness (TO) on sustainable energy consumption. Combining these insights with the strategic policy measures outlined in Resolution No. 55-NQ/TW and Resolution No. 136/NQ-CP, the study offers actionable recommendations to expedite Vietnam's transition towards renewable energy targets set for 2030 and 2045.